Síntese e caracterização de nanocristais de TiO2. Avaliação de sua biocompatibilidade através de implantes intraósseos - Almeida, Ronaldo José de (2011)
The success of alloplastic bone grafts is still limited because of inadequate osseointegration. In this study, TiO2 nanocrystals (21 nanometers) were synthesized by wet-chemical co-precipitation Their structure, size and purity were determined by Raman spectroscopy (RAMAN) and x-ray diffraction (XRD). Optical microscopy was used to evaluate inflammation arising from intraosseous implants in guinea pigs as recommended by the World Dental Federation (FDI). Ten guinea pigs were used receiving two implants each. Half of the guinea pigs were observed at four weeks and the rest at twelve weeks. 24 slides were prepared with 144 histological cuts, stained with hematoxylin-eosinand and analyzed for inflammation response by two independent observers. It was determined that inflammation was absent/mild at both time periods due to low cellular variability and direct and structural bone apposition on and around the material without visible separation or signs of rejection. These characteristics were observed in all samples. Nanotopography analysis and Atomic Force Microscopy (AFM) showed integration between the new bone and the implanted material. Therefore, through the methodology used, it was possible to evidence osseointegration and biocompatibility in alloplastic material at the nanoscale.